Scarlet - Gaughen, A. C. (New York : Walker, 2012)
Will Scarlet shadows Robin Hood, with an unerring eye for finding treasures to steal and throwing daggers with deadly accuracy, but when Gisbourne, a ruthless bounty hunter, is hired by the sheriff to capture Robin and his band of thieves, Robin must become Will's protector risking his own life in the process.
Includes bibliographical references and filmography.
School Library Journal
Voice of Youth Advocates (V.O.Y.A.)
School Library Journal, February 2012
Voice of Youth Advocates (V.O.Y.A.), December 2011
Young Adult.
Keywords: Friendship -- Juvenile Fiction; Robin Hood (Legendary character) -- Juvenile Fiction; Friendship -- Fiction; Robin Hood (Legendary character) -- Fiction; Friendship -- Fiction; Robin Hood (Legendary character) -- Fiction